TEACHING CONTROVERSIAL HISTORICAL EVENTS: PEDAGOGICAL STRATEGIES AND STUDENT OUTCOMES - Fahruddin, Fahruddin (Jurnal Pendidikan Sejarah Indonesia, 2024)
Abstract: This study aims to analyse the effectiveness of inquiry-based interactive pedagogical learning strategies in improving students' engagement and knowledge retention in controversial history lessons. The research method used was mixed methods. The research was conducted in five schools in Yogyakarta and Bantul, with the research population consisting of 500 students and 10 history teachers divided into experimental and control classes. The research instruments used included the use of the Engagement Measurement Tool and Knowledge Retention Test to collect quantitative data, as well as classroom observations and interviews to collect qualitative data. The validity of the instruments was tested through an expert panel and confirmatory factor analysis (CFA), while reliability was measured using Cronbach's Alpha coefficient. Quantitative data was analysed using descriptive statistics and ANOVA tests to compare the improvement in engagement and knowledge retention between the experimental and control classes. Qualitative data were analysed using thematic analysis method to identify patterns and main themes. The results showed that students in the experimental class experienced significant increases in engagement (20percent) and knowledge retention (25percent), compared to smaller increases in the control class (5percentand 8percentrespectively). Observations and interviews supported these findings by showing that students in the experimental class were more active and motivated in learning history. This research contributes to existing knowledge by providing empirical evidence on the effectiveness of inquiry-based interactive pedagogical learning strategies, as well as offering practical implications for educators and policy makers to improve the quality of history education. The findings also highlight the need for further research covering a wider population and various educational contexts to understand the sustained impact of this teaching strategy. Abstrak: Penelitian ini bertujuan untuk menganalisis efektivitas strategi pembelajaran pedagogis interaktif berbasis inkuiri dalam meningkatkan keterlibatan siswa dan retensi pengetahuan dalam pelajaran sejarah kontroversial. Metode penelitian yang digunakan adalahmetode campuran. Penelitian ini dilakukan di lima sekolah di Yogyakarta dan Bantul, dengan populasi penelitian terdiri dari 500 siswa dan 10 guru sejarah yang dibagi menjadi kelas eksperimen dan kontrol. Instrumen penelitian yang digunakan meliputi penggunaan Alat Pengukuran Keterlibatan dan Tes Retensi Pengetahuan untuk mengumpulkan data kuantitatif, serta observasi kelas dan wawancara untuk mengumpulkan data kualitatif. Validitas instrumen diuji melalui panel ahli dan analisis faktor konfirmatori (CFA), sementara reliabilitas diukur menggunakan koefisien Cronbach’s Alpha. Data kuantitatif dianalisis menggunakan statistik deskriptif dan uji ANOVA untuk membandingkan peningkatan keterlibatan dan retensi pengetahuan antara kelas eksperimen dan kontrol. Data kualitatif dianalisis menggunakan metode analisis tematik untuk mengidentifikasi pola dan tema utama. Hasil penelitian menunjukkan bahwa siswa di kelas eksperimen mengalami peningkatan signifikan dalam keterlibatan (20persen) dan retensi pengetahuan (25persen), dibandingkan dengan peningkatan yang lebih kecil di kelas kontrol (5persendan 8persen masing-masing). Observasi dan wawancara mendukung temuan ini dengan menunjukkan bahwa siswa di kelas eksperimen lebih aktif dan termotivasi dalam belajar sejarah. Penelitian ini berkontribusi pada pengetahuan yang ada dengan memberikan bukti empiris tentang efektivitas strategi pembelajaran pedagogis interaktif berbasis inkuiri, serta menawarkan implikasi praktis bagi pendidik dan pembuat kebijakan untuk meningkatkan kualitas pendidikan sejarah. Temuan ini juga menyoroti kebutuhan untuk penelitian lebih lanjut yang mencakup populasi yang lebih luas dan berbagai konteks pendidikan untuk memahami dampak berkelanjutan dari strategi pengajaran ini.